Effectiveness of oral zinc therapy as an adjunct to intralesional measles, mumps, and rubella vaccine in patients of verruca vulgaris - Sonia P Jain; Dhaval Kumar Bansode; Shantanu S Harode; Pratiksha Sonkusale (Wolters Kluwer Medknow Publications, 2024)
Background: Verruca vulgaris (VV) is caused by human papillomavirus affecting both keratinized and nonkeratinized epithelium. Different treatment modalities are available leading to scarring, pain, and ineffectiveness. Injection of measles, mumps, and rubella (MMR) not only clears treated warts but also distant warts by stimulating cell-mediated immunity. Objectives: The objective of this study was to study the efficacy of adjuvant zinc with injectable MMR vaccine in treatment with side effects of treatments, the pattern of regression, the number of injections required for clearance, and the recurrence of verruca. Materials and Methods: Fifty patients having verruca were divided into groups A and B with 25 patients each. Group A received an injection of MMR and tablet of zinc whereas group B only injection MMR. A total of five injections were given in the largest wart at intervals of 2 weeks i.e., 0, 2, 4, 6, and 8 weeks. Follow-up was done at 3rd month and 6th months following 1st dose. Improvement in warts and patient satisfaction were assessed using visual analog scale and Likert scale, respectively. Results: Mean age of patients in groups A and B was 30.36 and 32.68 with male-to-female ratio 5.28:1 (21:4) and 1.77:1 (16:9), respectively. Mean numbers and size of lesions in group A and B were 2.24 (±1.59), 1.84 (±1.40) and 5.52 mm, 5.08 mm, respectively. Eighty-four percentage of patients in both groups needed five injections for complete clearance. Pain was the most common side effect in all patients of both groups whereas gastritis, fever, and lymphadenopathy were observed only in one patient of Group A. Patients in both groups were strongly satisfied on Likert's scale. Conclusion: Oral zinc as an adjuvant with MMR vaccine for the treatment of VV was equally safe but did not prove to be of higher efficacy in our study.